Psoriasis (chronic plaque) - Naldi, Luigi (BMJ Publishing Group, 2009)
INTRODUCTION: Psoriasis is a chronic inflammatory skin disease that affects 1% to 3% of the population, in some people causing changes to the nails and joints as well as skin lesions. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical questions: What are the effects of non-drug (other than ultraviolet light), topical drug, ultraviolet light, and systemic drug treatments for chronic plaque psoriasis? What are the effects of combined treatment with drugs plus ultraviolet light for chronic plaque psoriasis? What are the effects of combined systemic plus topical drug treatments for chronic plaque psoriasis? We searched: Medline, Embase, The Cochrane Library, and other important databases up to August 2007 (Clinical Evidence reviews are updated periodically; please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 122 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review we present information relating to the effectiveness and safety of the following interventions: acupuncture, adding calcipotriol (topical) to psoralen plus ultraviolet light A or ultraviolet light B, adding oral retinoids to psoralen plus ultraviolet A (PUVA), alefacept, balneotherapy, ciclosporin, dithranol, T cell-targeted therapies, cytokine blocking agents, emollients (alone or plus ultraviolet light B), etanercept, fish oil supplementation, fumaric acid derivatives, Goeckerman treatment, heliotherapy, infliximab, Ingram regimen, keratolytics (salicylic acid, urea), leflunomide, methotrexate, oral pimecrolimus, oral retinoids (alone or with ultraviolet light B), phototherapy plus balneotherapy, psoralen plus ultraviolet A, psychotherapy, systemic drug treatments plus topical vitamin D derivatives, tars, tazarotene, topical corticosteroids (alone or plus oral retinoids), topical Vitamin D derivatives, ultraviolet light A, and ultraviolet light B.